2020
DOI: 10.1186/s13033-020-0340-5
|View full text |Cite
|
Sign up to set email alerts
|

Stigma towards people with a diagnosis of severe mental disorder in primary healthcare centers: perspectives of service users and health teams in Chile

Abstract: Background: Stigma towards people diagnosed with a severe mental disorder (SMD) is one of the main obstacles for these service users to receive timely and relevant healthcare. This study was undertaken to understand how stigmatizing attitudes are demonstrated towards people with SMD in primary healthcare centers (PHC) from the perspective of those affected and primary healthcare professionals. Methods: We used a qualitative exploratory research design to contrast the differences and similarities regarding stig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
(47 reference statements)
1
15
0
Order By: Relevance
“…Moreover, it was found that secondary care health personnel present a lower level of stigma than do primary care personnel in both dimensions of the EAPS-TM scale. This result is consistent with the research that reports greater stigma in primary care (Mittal et al, 2014) and reinforces the research that shows that in Chile, there are negative attitudes toward mental health users by primary care health personnel (Vaccari et al, 2020;Vistorte et al, 2018). This may be because primary care personnel have less information and contact with people who receive a psychiatric diagnosis.…”
Section: Relationship Between Stigma and Sociodemographic Variablessupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, it was found that secondary care health personnel present a lower level of stigma than do primary care personnel in both dimensions of the EAPS-TM scale. This result is consistent with the research that reports greater stigma in primary care (Mittal et al, 2014) and reinforces the research that shows that in Chile, there are negative attitudes toward mental health users by primary care health personnel (Vaccari et al, 2020;Vistorte et al, 2018). This may be because primary care personnel have less information and contact with people who receive a psychiatric diagnosis.…”
Section: Relationship Between Stigma and Sociodemographic Variablessupporting
confidence: 90%
“…However, the exercising of health rights is limited by stigma. In addition, there is little but consistent information showing that health personnel in Chile stigmatize users (Vaccari et al, 2020;Vistorte et al, 2018). These reasons have led the Ministry of Health (MINSAL) to include stigma within the National Mental Health Plan 2017-2025 as a relevant program line (MINSAL, 2017).…”
Section: Mental Health In Chilementioning
confidence: 99%
“…Therefore, interventions to reduce stigma towards people diagnosed with mental disorders specifically targeted towards health professionals are being promoted [1]. Ingredients such as information about mental disorders, development of specific skills, and modifications in the culture of the health centres have been pointed out as the most effective [18].…”
Section: Introductionmentioning
confidence: 99%
“…More recently [32] the protocol of an integrative programme to reduce stigma in Chilean healthcare workers from 11 primary care centres has been published. The intervention is based on previous qualitative analyses carried out with service users and health teams [18]. The project consists of education strategies, direct (facilitators will have a diagnosis of mental disorder), and indirect contact (videos and narratives) with people diagnosed with severe mental disorders, and skill development.…”
Section: Introductionmentioning
confidence: 99%
“…However, during the past 20 years, public stigma has not improved with the increased knowledge about mental disorders [ 10 ]. Stigma was reported in the healthcare providers even though they may gain more knowledge than the general population [ 11 ]. A previous study pointed out stigma would better be addressed in the early years of professional learning [ 12 ].…”
Section: Introductionmentioning
confidence: 99%